Culture-Bound Collocations in Bestsellers: A Study of Their Translations from English into Turkish - Dinçkan, Yeşim (Meta, 2010)
This paper discusses the treatment of culture-bound collocations in translations of three recent English bestsellers into Turkish. The findings are categorized as per the nature of the example and translation strategy, and they are further discussed within the framework of domestication and foreignizing. Factors that may affect translators, such as context, the demands of publishers in Turkey and the genre of the novels – bestsellers – and the relations between best-sellerization, popular fiction, and translation are also discussed. The conclusion includes reflections concerning the consistency in the choices of translators, the least preferred strategies and eleven factors that may affect the translators of bestsellers. It is argued that the fact that the source language is English and the source books are bestsellers have affected the choices of the translators. In conclusion, some suggestions in reference to the translation of bestsellers are made and it is emphasized that not only translations of classical literature, but also of popular fiction constitute a fruitful field of study for translation scholars.